Computational assessment of the cellular dosimetry and microdosimetry of the gadolinium electrons released during neutron capture therapy. (24th January 2019) - Golshani, Masud; Mowlavi, Ali Asghar; Azadegan, Behnam
Abstract: One of the challenges in radiobiology is the determination of the dose of Auger electrons in cellular-molecular dimensions and evaluation of their relative biological effectiveness (RBE). In this study, we try to assess the cellular dosimetry and microdosimetry of the internal conversion (IC) and Auger electrons released during Gadolinium-157 neutron capture reaction ( 157 GdNCR) using the low-energy physics models included in Geant4 toolkit and MCNPX code. The results show that the MCNPX code does not have reliable results for the cellular dosimetry of low-energy electrons compared to the validated low-energy Geant4 physics models. Although the use of the Geant4-DNA models is a necessity in microdosimetric calculations, due to the time-consuming run of the Geant4-DNA models in the cellular dosimetry calculations, the use of Geant4-Penelope and Geant4-Livermore models can lead to the quick and reliable results. The results show that, with appropriate selection of physical parameters, the results of small-scale microdosimetry calculated using the CH models in Geant4 approach the results of Geant4-DNA. With regard to the cellular dosimetry results, the amount of the absorbed dose in the nucleus of a cell is strongly dependent on the distribution of Gd in the different compartments of the cell. The cross-dose in the nucleus from the Gd electrons released in adjacent cells is comparable to the self-dose of the nucleus to nucleus and noteworthy to destroy the quiescent cancer cells that do not accumulate Gd. The microdosimetry results show that, unlike the absorbed dose in DNA, RBE is not much dependent on the Gd distribution relative to the DNA within the molecular dimensions. If Gd is distributed at the center of the DNA, the absorbed dose of Gd electrons in the DNA (246 kGy) with a quality-factor-equivalent RBE of 7.93 is sufficiently large for the double-strand breaks (DSBs) of the DNA.